A world history of ancient political thought - Black, Antony (Oxford : Oxford University Press, 2009)
This text examines the political thought of China, Greece Israel, Rome, India, Iran, Egypt, Mesopotamia, and also early Christianity. Each of these had its own priorities, based on a religious and philosophical perspective. This led to different ideas about who should govern, how to govern, and what government was for.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Political science -- Philosophy -- History; World politics; State, The -- Origin; Civilization, Ancient -- Political aspects